39 ECHOCARDIOGRAPHIC FINDING BETWEEN PATIENTS WITH HEART FAILURE WITH REDUCED EJECTION FRACTION IN TREATMENT WITH ARNI AND SGLT2I. (15th December 2022) - Ceci, Vincenzo; Mazzeo, Pietro; Ferrara, Salvatore; Nardella, Luigi; Tricarico, Lucia; Alfieri, Simona; Croella, Francesca; Amatruda, Marco; Granatiero, Michele; D´alessandro, Damiano; Di Nunno, Nicola; Pugliese, Rosanna; et al.
Abstract: Background: Cardiac remodelling is an adverse phenomenon linked to heart failure progression. Cardiac remodelling could represent the real therapeutic goal in the treatment of patients with heart failure with reduced ejection fraction (HFrEF), being potentially reversed through different pharmacotherapies. Currently, there are well-established drugs such as angiotensin-converting enzyme inhibitors/angiotensin II receptor blockers and β-blockers with anti-remodelling effects; recently, angiotensin receptor neprilysin inhibitor effects on inhibiting cardiac remodelling were demonstrated. Benefits of gliflozins on left ventricular hypertrophy, dilation, and systolic and diastolic function were also described. Aim of study: to evaluate possible echocardiographic differences between patients with HFrEF in treatment with ARNI or SGLT2I and patients with HFrEF in therapy with ARNI plus SGLT2i. Materials: Between June 2021 and April 2022, consecutive patients with HFrEF underwent to conventional and advanced echocardography (TDI, 2DSTE). After 3 month, these patients underwent to echocardiographic follow-up. Results: 76 patients (68 male, 66, 51±9, 68 years old) with HFrEF were enrolled in the study. After 3 month of therapy, there was an inverse relation between number of HFrEF drugs (0, 1 or 2) and echocardiographic parameters [E/E' (r: -0, 28; p: 0, 036) and E/A (r: -0, 37; p: 0, 012)]. Conclusions: About cardiac remodelling, there are not significant echocardiographic differeces but a better trend for the diastolic dysfunction in patients with HFrEF in treatment with ARNI plus SGLT2i vs HFrEF patients in therapy with ARNI or SGLT2i was showed.